A systematic method to detect the metabolic threshold from gas exchange during incremental exercise - Dolezal, B. A.; Storer, T. W.; Neufeld, E. V.; Smooke, S.; Tseng, C.-H.; Cooper, C. B. (Journal of Sports Science & Medicine, 2017)
Incremental exercise consists of three domains of exercise intensity demarcated by two thresholds. The first of these thresholds, derived from gas exchange measurements, is defined as the metabolic threshold (VO2) above which lactate accumulates. Correctly and reliably identified, VO2 is a non-invasive, sub-maximal marker of aerobic function with practical value. This investigation compared variability in selection of VO2 among interpreters with different levels of experience as well as from auto-detection algorithms employed by a commercially available metabolic cart (MC). Ten healthy young men performed three replicates of incremental cycle exercise during which gas exchange measurements were collected breath-by-breath. Two experienced interpreters (E) and four novice interpreters (N) determined VO2 from plots of specific response variables. Interpreters noted methods used and confidence in their selections. VO2 was automatically determined by the MC. Interclass correlations indicated that E agreed with each other (mean difference, 21 mL·min-1) and with the MC (23 mL·min-1), but not with N (-664 to 364 mL·min-1); N did not agree among themselves. Despite good overall agreement between E and MC, differences >500 mL·min-1 were seen in 50% of individual cases. N expressed unduly higher confidence and used different VO2 selection strategies compared with E. Experience and use of a systematic approach is essential for correctly identifying VO2. Current guidelines for exercise testing and interpretation do not include recommendations for such an approach. Data from this study suggests that this may be a serious shortcoming. Until an alternative schema for VO2 etection is developed prospectively, strategies based on the present study will give practitioners a systematic and consistent approach to threshold detection